2007
DOI: 10.1021/jf071308d
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Quantification of Provitamin D 2 and Vitamin D 2 in Hop (Humulus lupulus L.) by Liquid Chromatography–Diode Array Detection–Electrospray Ionization Tandem Mass Spectrometry

Abstract: In this work, ergosterol and ergocalciferol were identified for the first time in hop. In addition, in this article, a simple and reliable analytical methodology for analysis of these compounds in different commercial forms of hop is presented. The performance of the method was assessed by the evaluation of parameters such as absolute recovery (higher than 70%), repeatability (lower than 3 %), linearity ( r(2) > 0.9988) and limits of detection (ranging from 0.034 for ergocalciferol to 0.058 mg/L for ergosterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
1
13
1
Order By: Relevance
“…Although fungal infection was not tested for in our study, the vitamin D 2 content found in the plants may have been due to fungal contamination [ 42 ]. Vitamin D 2 is considered a marker for fungal contamination in some crops, such as ryegrass ( Lolium perenne L.) and hops ( Humulus lupulus L.) [ 43 , 44 ]. Vitamin D 3 and, in some cases, 25(OH)D 3 have previously been detected in the leaves of tomato [ 24 , 25 , 26 ], waxy leaf nightshade [ 23 , 25 ], potato [ 24 ], day blooming jasmine [ 27 ], zucchini [ 24 ], and alfafa [ 28 ]; however, we did not detect these metabolites in our samples of native Australian plants and detected only very low levels in seaweed.…”
Section: Discussionmentioning
confidence: 99%
“…Although fungal infection was not tested for in our study, the vitamin D 2 content found in the plants may have been due to fungal contamination [ 42 ]. Vitamin D 2 is considered a marker for fungal contamination in some crops, such as ryegrass ( Lolium perenne L.) and hops ( Humulus lupulus L.) [ 43 , 44 ]. Vitamin D 3 and, in some cases, 25(OH)D 3 have previously been detected in the leaves of tomato [ 24 , 25 , 26 ], waxy leaf nightshade [ 23 , 25 ], potato [ 24 ], day blooming jasmine [ 27 ], zucchini [ 24 ], and alfafa [ 28 ]; however, we did not detect these metabolites in our samples of native Australian plants and detected only very low levels in seaweed.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the plant is used in the brewing industry to add bitterness and aroma to beer 12,13 . Hops are very rich sources of prenylflavonoids, which are secreted along with bitter acids and essential oils by the lupulin glands of the inflorescences 12 . Xanthohumol (XN) is the main prenylflavonoid of hops (0.2-1.1%, w/w).…”
Section: Introductionmentioning
confidence: 99%
“…The hop plant (Humulus lupulus L.) is a dioecious plant of the Cannabacea family, cultivated in most temperate sones of the world for its female inflorescences. Nowadays, the plant is used in the brewing industry to add bitterness and aroma to beer 12,13 . Hops are very rich sources of prenylflavonoids, which are secreted along with bitter acids and essential oils by the lupulin glands of the inflorescences 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Although fungal infection was not tested for in our study, the vitamin D2 content found in the plants may have been due to fungal contamination [31]. In fact, vitamin D2 is considered a marker for fungal contamination in some crops, such as ryegrass (Lolium perenne L.) and hops (Humulus lupulus L.) [32,33]. Vitamin D3 and, in some cases, 25(OH)D3 have previously been detected in the leaves of tomato [13][14][15], waxy leaf nightshade [12,14], potato [13], day blooming jasmine [16], zucchini [13] and alfafa [17]; however, we did not detect these metabolites in our samples of native Australian plants, and only very low levels in seaweed.…”
Section: Discussionmentioning
confidence: 93%